Is Conventional Horizontal Strabismus Surgery Still a Valid Option in High Myopia? - Maurer, Lene; Palmowski-Wolfe, Anja (Klinische Monatsblätter für Augenheilkunde, 2025)
Background Surgical methods to join extraocular muscles are now often used to reduce the risk of scleral perforation in strabismus surgery, but published results indicate that the outcome is highly variable. We therefore wanted to assess whether conventional horizontal strabismus surgery is still a valid option in high myopia.Patients and Methods A retrospective chart review of patients with high myopia, defined as a spherical equivalent of ≥ − 6.0 D in at least one eye, and who had undergone conventional horizontal strabismus surgery was performed. Exotropic angles were converted to positive angles to summarize the results.Results 22 patients were analyzed (15 corrected for esotropia, 7 for exotropia). Prior to surgery, the mean angle of deviation, measured with the alternate prism cover test, was 33.9 prism diopters (PD; range 13 – 75 PD) at distance and 35.3 PD (range 8 – 75 PD) at near. Three months post-surgery, the overall mean dose effect (DE in PD/mm surgery) was 2.8 (standard deviation [SD] 0.5) at distance and 2.9 (SD 0.6) at near. In esotropia, the mean DE was 3.0 at both distance and near; in exotropia, the mean DE was 2.3 at distance and 2.5 at near. There were no major complications such as scleral perforations or retinal detachment.Conclusion Our data show that conventional horizontal strabismus surgery in high myopia is feasible, is not linked to an increased risk of scleral perforation, and offers predictable results.
Keywords: high myopia; conventional horizontal strabismus surgery; dose effect; exotropia; esotropia; posterior fixation suture